Prognostic significance of lymphocyte‐to‐monocyte ratio in diffuse large B‐cell lymphoma: a systematic review and meta‐analysis. Issue 6 (4th May 2016) - Xia, Wen‐Kai; Lin, Qing‐Feng; Shen, Dong; Liu, Zhi‐Li; Su, Jun; Mao, Wei‐Dong
Abstract : Published evidence on the prognostic significance of lymphocyte‐to‐monocyte ratio (LMR) in diffuse large B‐cell lymphoma (DLBCL) is controversial. We performed an updated meta‐analysis from 12 reports with 5021 patients to more accurately evaluate the prognostic value of LMR in DLBCL. Herein, we confirmed that patients with low LMR had shorter overall survival and progression‐free survival than those with high LMR in DLBCL. Subgroup analyses indicated that patient source, cut‐off values of LMR, treatment methods, and sample size showed similar prognostic performance in DLBCL patients. No significant heterogeneity was observed for progression‐free survival (PFS, P het = 0.192) among the enrolled studies. The meta‐analysis suggests that the LMR may be a potential biomarker in the prediction of clinical outcomes for DLBCL patients. Abstract : We performed an updated meta‐analysis from 12 reports with 5021 patients to more accurately evaluate the prognostic value of lymphocyte‐to‐monocyte ratio (LMR) in diffuse large B‐cell lymphoma (DLBCL), and confirmed that low LMR was associated with worse outcome in DLBCL patients. Our study supports the suggestion that the LMR may be a potential biomarker in the prediction of clinical outcomes for DLBCL patients.